Pengaruh Strategi Role Reversal Question Terhadap Hasil Belajar Siswa Kelas V Pada Mata Pelajaran Akidah Akhlak Di MI Al Hidayah NW Lendang Damai Lombok Barat - Erlan, Erlan; Sudrajat, Husaen; Syamsuddin, Syamsuddin (BALE LITERASI, 2025)
This study investigates the use of the Role Reversal Question Strategy method in Akidah Akhlak learning and its impact on improving student learning outcomes. The type of research used is the type of experimental research. In this study, the research approach used was a quantitative approach. The sample in this study was all 20 students of grade V Madrasah Ibtidaiyah NW Lendang Damai. The research time was carried out in the odd semester of the 2020/2021 academic year. To obtain data on student learning outcomes after being treated with role reversal question strategies in the Akidah Akhlak class V subject of Madrasah Ibtidaiyah NW Lendang Damai for the 2020/2021 academic year.The results showed that the use of the Role Reversal Question method had a significant positive impact on increasing students' understanding of the Akidah Akhlak subject matter. Students can be more active in finding solutions to problems given during learning. This finding is consistent with Mel Silberman's view that the Role Reversal Question method is one effective active learning approach. Therefore, recommendations are given to teachers to consider the use of more interactive learning strategies and focus on the active role of students in the learning process in order to improve student learning outcomes in the future